Efficacy of Acetazolamide in Refractory Epilepsy Management: A Quasi-Experimental Study - Zamir, Muhammad Ahmed; Alam, Naveed; Iqbal, Javed; Rehman, Muhammad Ali; Raza, Baqar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the efficacy of Acetazolamide in refractory epilepsy management. Study Design: Quasi-experimental study. Place and Duration of Study: Outpatient Neurology Department, Allied Hospital, Faisalabad Pakistan, from Sep 2020 to Feb 2021. Methodology: Using a non-probability consecutive sampling technique, 260 patients of either gender aged 18 to 60 years who met the criteria of refractory epilepsy were included in the study. Group-A (n=130) received oral Acetazolamide (250 mg twice a day) plus standard antiepileptic drugs, and Group-B (n=130) received a placebo plus standard antiepileptic drugs. Patients were assessed every four weeks for a six-month response to treatment. The outcome was assessed in terms of control of refractory epilepsy. Results: Acetazolamide was effective in 88(68.2%) patients compared to Placebo Group, which showed efficacy in 41(31.8%) patients (p-value was <0.001). In addition, the mean change in the number of attacks after treatment was significantly different between Group-A (2.9±1.5) versus Group-B (1.6±1.6) (p-value <0.001). Conclusion: Acetazolamide is effective in treating refractory epilepsy.